Die Zukunft der Milch-Lieferbeziehungen aus Sicht deutscher Landwirte; The Future of Milk Delivery Relations from the Perspective of German Farmers - Julian Petersen; Sebastian Hess (German Journal of Agricultural Economics (GJAE), 2018)
Die Lieferbeziehungen zwischen Milcherzeugern und Molkereien in Deutschland sind möglicherweise nur eingeschränkt geeignet, um Preissignale in ein entsprechendes Mengen-Management zu überführen. Dies ist einer der Gründe, warum eine Reformierung der Lieferbeziehungen immer wieder gefordert wird. Es ist jedoch nur wenig über die Präferenzen deutscher Milcherzeuger im Hinblick auf die von ihnen bevorzugten Attribute eines möglichen Milchliefervertrags bekannt. Zufällig ausgewählte Landwirte in unterschiedlichen deutschen Regionen wurden daher zu diesem Thema befragt. Anhand von Choice-Experimenten wurden ihre Präferenzen hinsichtlich unterschiedlicher Vertragsattribute wie Laufzeit, Preisfindung, Kündigungsfrist und Mengenregelung bestimmt, indem ein Random-Parameter-Logit-Modell geschätzt wurde. Die Ergebnisse verweisen auf starke regionale Heterogenität. Insgesamt wünschen sich größere Milcherzeuger eher vertragliche Lösungen, während kleine und mittlere Betriebe eher am typischen Liefermodell ohne Mengenbindung festhalten wollen. Die meisten Landwirte wünschen sich jedoch kürzere Kündigungsfristen bei ihrer Molkerei. Milcherzeuger in ostdeutschen Bundesländern lehnen das typische Liefermodell deutlich häufiger ab als Befragte in Westdeutschland (Quelle: Verlag). SW: Lieferbeziehungen; Genossenschaften; Choice-Experimente; Milchpaket; Agrarpolitik Zitierte Vorschriften u.a.: Verordnung (EU) Nr. 261/2012;In typical contractual relations between milk producers and processors in Germany, prices may currently function only to a limited extend as signals for quantity adjustments of milk production. This is one of the reasons why a reform of the contractual relationships has been frequently discussed. However, little is known about the preferences of German milk producers regarding their preferred attributes of an ideal milk delivery relationship. Therefore, randomly selected farmers in different German regions where presented with Discrete-Choice-Experiments about different contractual attributes such as duration, pricing, cancellation period and quantity regulation. A random parameter logit model was estimated to identify drivers of preference heterogeneity. Results indicate that larger milk producers tend to favor fixed contractual solutions, while small and medium-sized producers tend to adhere to the currently prevailing cooperative delivery system of unregulated quantities of delivery and ex post pricing. However, the majority of milk producers want shorter cancellation periods with their dairy companies, and milk producers in East German federal states reject the typical cooperative delivery system more frequently than the respondents in West Germany. – – In typical contractual relations between milk producers and processors in Germany, prices may currently function only to a limited extend as signals for quantity adjustments of milk production. This is one of the reasons why a reform of the contractual relationships has been frequently discussed. However, little is known about the preferences of German milk producers regarding their preferred attributes of an ideal milk delivery relationship. Therefore, randomly selected farmers in different German regions where presented with Discrete-Choice-Experiments about different contractual attributes such as duration, pricing, cancellation period and quantity regulation. A random parameter logit model was estimated to identify drivers of preference heterogeneity. Results indicate that larger milk producers tend to favor fixed contractual solutions, while small and medium-sized producers tend to adhere to the currently prevailing cooperative delivery system of unregulated quantities of delivery and ex post pricing. However, the majority of milk producers want shorter cancellation periods with their dairy companies, and milk producers in East German federal states reject the typical cooperative delivery system more frequently than the respondents in West Germany.
Keywords: 330